1999
DOI: 10.1111/j.1939-1676.1999.tb01137.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 131 I‐Induced Hypothyroidism on Indices of Reproductive Function in Adult Male Dogs

Abstract: Hypothyroidism has been cited as a cause of infertility, abnormal semen quality, and poor libido in people and animals. The purpose of this study was to evaluate the effect of hypothyroidism on variables indicative of reproductive function in adult male dogs. Nine normal dogs were randomly assigned to 2 groups. Hypothyroidism was induced with 131 I in 6 dogs. Three dogs remained untreated, normal, and euthyroid. Thyroid hormone concentrations, body weight, clinical signs, and reproductive function were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, we conclude that primary or secondary hypothyroidism can be excluded in these dogs, as basal TSH concentrations were at physiological levels and TRH injection induced a clear TSH increase in all dogs of this breed. Normal semen quality, in contrast, is not a relevant parameter as regards thyroid assessment, as Johnson et al (1999) reported that no relation exists between hypothyroidism and disturbed fertility in male dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we conclude that primary or secondary hypothyroidism can be excluded in these dogs, as basal TSH concentrations were at physiological levels and TRH injection induced a clear TSH increase in all dogs of this breed. Normal semen quality, in contrast, is not a relevant parameter as regards thyroid assessment, as Johnson et al (1999) reported that no relation exists between hypothyroidism and disturbed fertility in male dogs.…”
Section: Discussionmentioning
confidence: 99%
“…However, work by C. Johnson, et al (1999) in Beagles failed to document any deleterious effect of experimentally induced hypothyroidism on any aspect of male reproductive function. However, work by C. Johnson, et al (1999) in Beagles failed to document any deleterious effect of experimentally induced hypothyroidism on any aspect of male reproductive function.…”
Section: Reproductive Signsmentioning
confidence: 97%
“…However, in dogs, extragonadal sperm reserves are rarely completely depleted in the course of 5-7 days. In the work of Johnson et al (1999), extragonadal sperm reserves in dogs became completely depleted after 10.5 days on average. In general, total sperm counts in ejaculates from healthy adult dogs should reach 200-300 million to 1 billion.…”
Section: Discussionmentioning
confidence: 99%